Analisis Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Pendapatan Asli Daerah dengan Variabel Moderasi Jumlah Penduduk pada Kabupaten Manggarai - Maria Herlina Novali Ngangu; Maria I. Hewe Tiwu; Cicilia A. Tungga (Universitas Veteran Bangun Nusantara, 2024)
This research aims to examine the influence of Regional Taxes and Regional Levies on Original Regional Income (PAD) in Manggarai Regency, as well as the role of Population as a moderating variable using various regression models. The analysis includes simple regression, regression with interaction (MRA), as well as the T test and F test to test the significance of independent variables on PAD. The results show that Regional Taxes and Population have a significant influence on PAD, while Regional Levies do not have a significant influence. The regression model moderated by population reveals that the interaction with regional taxes strengthens its influence on PAD. However, population does not moderate the influence of regional levies on PAD. Overall, these models can explain most of the variation in PAD, with R2 reaching 75.5% up to 80.3%. Hypothesis testing shows that simultaneously, Regional Taxes, Regional Levies, and Population have a significant effect on PAD with an Adjusted R Square value of 0.603. The partial test also shows the significance of the regression model, with Regional Taxes and Population each having significant influence on PAD, while Regional Levies do not have a partially significant influence. The results of this research are in line with several previous studies which show that Regional Taxes and population have a significant impact on PAD, while the influence of Regional Levies is not significant.